KETERLAMBATAN PENANGANAN PESERTA BPJS KESEHATAN OLEH PIHAK RUMAH SAKIT YANG MENGAKIBATKAN KEMATIAN - Nanda Aditya Permana (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT This research wants to solve the problem that often occurs in hospital Samarinda, like late handling patients who used BPJS Health that makes decease, because there is different handling between general patient and BPJS patient. The hospital prefers general patients more than BPJS patients. This research used normative research or doctrinal law research, and library research. This normative research or doctrinal law research is like library research or document study. The research used the statutory approach or conceptual approach. Based research results show that laws in hospitals that late handling BPJS patients and make decease is warning verbal, warning list, forfeit, and revocation of the hospital. And more fatal is the hospital is reported to the authorities. The factor that influenced late handling BPJS patient in the hospital is level of competence of hospital apparatus, a medical device in a hospital, and organizational culture